The Indian Science Reports Portal: A Review - Das, Suman (Journal of Data Science, Informetrics, and Citation Studies)
The Indian Science Reports portal (www.indianscience.net) is an open access web portal designed to provide comprehensive resource analytics of India’s research capabilities at both the individual and institutional levels. The web portal was created by a group of computer scientists from Banaras Hindu University’s Computer Science Department, with funding from the Department of Science and Technology (DST), Government of India (Singh et.al. 2020) This appears to be an individual effort (Singh et.al. 2020) to create such a non-profit repository. The portal solely covered scientific research publications during 2010-2019 indexed with Dimensions.ai database. For measuring scientometric analysis the portal collected data from the Dimensions.ai database (fetching data on publications, patents, research grants, etc), Altmetric data (including social media presence), and Gender API. (Paswan, & Singh, 2020). Gender API categorizes authors’ gender diversity through the use of API (Application Programme Interface). There are nine broad variables, namely, research productivity, citations, collaboration, gender distribution, open access, social media visibility, SDG-related studies, important institutions, and grants, that are covered in a wide examination of Indian institutions and individual research productivity. The portal can be navigated through mainly six tabs, namely, Research Output, Citations, Collaboration, Gender Distribution, Open Access, and More. Research Output tab refers to Indian research output during 2010-2019. Citations tab refers to Citations received by Indian research output during 2010-2019. Collaboration tab refers to collaboration patterns in Indian research output. Gender Distribution tab refers to gender distribution of Indian research output. Open Access tab refers to open access availability of Indian research output. ‘More’ tab includes social media visibility of Indian research output, research grants volume, Indian research publications on sustainable development goals, comparison of indicators for major Indian institutions, and about 1000 institutional reports. The institutional reports include major public and private institutions in India.